The Effect of Immigration on Housing Prices in Vancouver - Yang, Ning (Université d'Ottawa | University of Ottawa, 2012)
This study examines the behavior of the housing prices in response to immigration activity in Vancouver and Toronto at census tract level based on the population censuses of 1996 to 2006. The results show that in Vancouver, immigration has a positive effect on the housing prices, an 1% point increase of the immigration share in the total population is associated with an increase in average dwelling values of 0.675%. As Toronto and Vancouver are two major English speaking census metropolitan areas (CMAs) with the largest number of immigrants, as a reference, the case of Toronto will be compared with the case of Vancouver. In Toronto a I% point increase of the immigration composition is coincident with an increase of the housing prices of 1.108%.